2016
DOI: 10.1063/1.4941434
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the influence of the intrinsic defects in Gd-doped ZnO thin-films

Abstract: Gd-doped ZnO thin films were prepared using pulsed laser deposition at different oxygen pressures and varied Gd concentrations. The effects of oxygen deficiency-related defects on the Gd incorporation, optical and structural properties, were explored by studying the impact of oxygen pressure during deposition and post-growth thermal annealing in vacuum. Rutherford Backscattering Spectrometry revealed that the Gd concentration increases with increasing oxygen pressure for samples grown with the same Gd-doped Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…The a-parameter increased while the c-parameter decreased with incorporation of Gd compared to without incorporation of Gd. DFT calculations confirmed that Gd-oxygen vacancy (V O ) complexes cause c-parameter contraction [25].…”
Section: Structural Propertiesmentioning
confidence: 69%
See 2 more Smart Citations
“…The a-parameter increased while the c-parameter decreased with incorporation of Gd compared to without incorporation of Gd. DFT calculations confirmed that Gd-oxygen vacancy (V O ) complexes cause c-parameter contraction [25].…”
Section: Structural Propertiesmentioning
confidence: 69%
“…We attributed this red band to O i and V Zn [32,33]. After a sample was annealed under vacuum conditions to create oxygen vacancies, a significant reduction in the red band was observed, while the spectrum of the vacuum-annealed sample became dominated by the green band (Figure 3(b)) [22,25]. …”
Section: Optical Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, the near band edge (NBE) free exciton emission is generally considered as an origin of UV emission in the room temperature PL spectra [4]. The well-known defect-based green emission band in ZnO PL spectra is ascribed to singly ionized oxygen vacancies by some and to other defects or impurities by others [5][6][7]. In other words, the exact origin of green emissions is still in dispute, although defects such as oxygen vacancies (V O ), oxygen interstitials (O i ), zinc vacancies (V Zn ), zinc interstitials (Zn i ) and oxide antisites (O Zn ) are suggested as origin of candidates [8].…”
Section: Introductionmentioning
confidence: 99%
“…Channeling experiments as well as photoluminescence studies [1,[3][4][5][6][7][8][9][10] indicate, that rare-earth elements in ZnO are preferentially incorporated at cation sites. The incorporation of Gd in the presence of intrinsic defects in ZnO could lead to the formation of stable compounds inside the crystal [11][12][13][14][15][16]. In particular, the formation of such complexes involving gadolinium and oxygen vacancies or zinc interstitials could promote ferromagnetism in ZnO as suggested in Refs.…”
Section: Introductionmentioning
confidence: 99%